Simulasi Manajemen Keperawatan Bencana Darurat Pada Siswa di SMA Bawakaraeng - Rusli Abdullah; Abd. Herman Syah Thalib; Ricky. Z; Yuliana Banapon; Tasik Bula (BADAN PENERBIT STIEPARI PRESS, 2023)
A disaster is an undesirable event that usually occurs suddenly and causes casualties. Indonesia is one of the countries most prone to disasters in the world, frequent and unpredictable, including earthquakes, tsunamis, landslides, volcanic eruptions, floods and droughts. affected by a disaster if this situation is not carefully anticipated by all elements of government and society. So it is necessary to carry out a Disaster Management Simulation, which is a process or strategy that is implemented before, during or after a type of disaster event occurs. The purpose of the counseling and simulations carried out is expected to increase students' knowledge and readiness in dealing with emergency disasters after appropriate simulations regarding emergency disaster nursing are carried out. The activities carried out are in the form of counseling and simulations using leaflets, teaching aids and simulations. There is an increase in students' knowledge of emergency disaster nursing as well as skills and preparedness for dealing with disasters. Thus, providing counseling and simulations to students at Bawakaraeng High School regarding emergency disaster nursing is very effective in increasing knowledge.